Semen Characteristics of Vaccinated Shikabrown Cocks Challenged with a Velogenic Newcastle Disease Virus - Rwuaan, J.S.; Rekwot, P.I.; Abdu, P.A.; Eduvie, L.O.; Obidi, J.A. (International Journal of Poultry Science, 2009)
Twenty-five cocks consisting of 14 red and 11 white Shikabrown cocks selected on the basis of body weight and antibody titres were infected with 0.2 ml of 106.0 EID50 of a velogenic Kudu 113 strain of Newcastle disease virus intranasally and intraocularly. Twenty-five cocks consisting of 14 red and 11 white Shikabrown cocks served as controls. Cloacal temperatures, live weights and semen samples of both control and infected cocks were taken weekly for six weeks. Semen was collected by abdominal message and evaluated for volume, colour, motility, concentration, percent live spermatozoa and percent total spermatozoa abnormalities. The semen volume of infected red cocks showed a general increase over that of control red cocks. The semen volume of the control white Shikabrown cocks was significantly (p